2004
DOI: 10.1097/00007691-200412000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Times for Monitoring Tacrolimus in Stable Adult Liver Transplant Recipients

Abstract: The aim of this study was to determine the most informative sampling time(s) providing a precise prediction of tacrolimus area under the concentration-time curve (AUC). Fifty-four concentration-time profiles of tacrolimus from 31 adult liver transplant recipients were analyzed. Each profile contained 5 tacrolimus whole-blood concentrations (predose and 1, 2, 4, and 6 or 8 hours postdose), measured using liquid chromatography-tandem mass spectrometry. The concentration at 6 hours was interpolated for each profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Models from previous studies were tested by using the Chinese liver transplant patients data in the present study, we found there was good correlation between AUC 0-12Pred and AUC 0-12Obs (r 2 = 0.880-0.928) [19][20][21][23][24][25] . The percentage of profiles for which PE fell within ±15% was similar compared with our equations (31.9-70.2%).…”
Section: Models Compared With Other Studysupporting
confidence: 54%
See 4 more Smart Citations
“…Models from previous studies were tested by using the Chinese liver transplant patients data in the present study, we found there was good correlation between AUC 0-12Pred and AUC 0-12Obs (r 2 = 0.880-0.928) [19][20][21][23][24][25] . The percentage of profiles for which PE fell within ±15% was similar compared with our equations (31.9-70.2%).…”
Section: Models Compared With Other Studysupporting
confidence: 54%
“…LSS studies were carried on in various transplant patients and different equations were obtained [15][16][17][18][19][20][21][22][23][24][25] . A useful LSS model should be accurate and precise in prediction and convenient for the TDM of patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations